HUBUNGAN ANTARA PRODUKTIVITAS PEKERJA GALANGAN DAN TEKNIK KERJA TERHADAP KINERJA GRAVING DOCK (STUDI KASUS DI PT. JANATA MARINA INDAH SEMARANG) - Suharto Suharto (Jurnal Teknik Sipil Unaya, 2015)
Shipyard industry  is one of the most  important chain  on the national shipping system. Notably to maintains the vessels condition in order to get adjustment of The Indonesia Classification Bureaustandard. Shipyard’s productivity depends on the graving dock capacity, man productivity and work method. Empirical studies show that man competiveness and productivity and effective work method are primary factors which affects choice rate from shipping companies to a shipyard. The research goal was to analyzed the effect of man productivity and work method toward graving dock performance in PT. Janata Marina Indah Semarang. Multiple linear  regression used as a method in this research. Methodology use basic is difficulty to identify relating directly from man productivity and work method toward graving dock performance. The sampling method using  purposive random sampling with 35 respondents who have long experience in the graving dock works. The result of regression analysis is:  Y= -0,357 + 0,256 X1 + 0,249 X2. The result shows that two factors both man productivity and work method, are have  significant effect toward graving dock performance.